Contrasting photosynthesis and photoinhibition in tetraploid and its autodiploid honeysuckle (Lonicera japonica Thunb.) under salt stress - Yan, Kun; Wu, Congwen; Zhang, Lihua; Chen, Xiaobing (Frontiers in Plant Science, 2015)
Honeysuckle (Lonicera japonica Thunb.) is a popular landscape plant. This study was to explore leaf photosynthetic characterization with emphasis on the coordination between photosystem II (PSII) and photosystem I (PSI) in tetraploid and its autodiploid honeysuckle (TH and DH) upon salt stress (300 mM NaCl). Leaf photosynthetic rate and carboxylation efficiency in DH and TH were significantly decreased under salt stress, and the decrease was greater in DH. PSII photoinhibition was induced in DH under salt stress, as the maximum quantum yield of PSII (Fv/Fm) was significantly decreased. PSII photoinhibition declined electron flow to PSI, but did not prevent PSI photoinhibition, as the maximal photochemical capacity of PSI (△MR/MR0) was significantly decreased by salt stress. According to the significant decrease in PSI oxidation amplitude in the first 1 s red illumination, PSI photoinhibition was more severe than PSII photoinhibition. As a result, PSII and PSI coordination was destroyed. Comparatively, salt-induced photoinhibition did not occur in TH, as no significant change was observed in Fv/Fm and △MR/MR0. Consequently, PSII and PSI coordination was not significantly affected by salt stress. In conclusion, TH maintained normal coordination between PSII and PSI by preventing photoinhibition and exhibited higher leaf photosynthetic activity than DH under salt stress. Compared with DH, lower leaf ionic toxicity due to greater root Na+ extrusion and restriction of Na+ transport to leaf might be responsible for maintaining higher leaf photosynthetic activity in TH under salt stress.